1999
DOI: 10.1016/s0960-894x(99)00236-x
|View full text |Cite
|
Sign up to set email alerts
|

An efficient stereoselective synthesis of [3S(1S,9S)]-3-[[[9-(benzoylamino)octahydro-6,10-dioxo-6H-pyridazino-(1,2-a)(1,2)-diazepin-1-yl]-carbonyl]amino]-4-oxobutanoic acid, an interleukin converting enzyme (ICE) inhibitor

Abstract: A series of phosphinic compounds mimicking the transition state of substrates hydrolysed by aminopeptidase N (EC 3.4.11.2) were synthesized. These new compounds have potent inhibitory activities with Ki values in the nanomolar range. These derivatives behave as the most potent APN inhibitors designed to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…For Ss APN, additional extended phosphinic analogs, which were at least tripeptides, reportedly exhibited similar levels of inhibition. 55 , 56 Doubled modifications were less favorable for Nm APN than for Ss APN, possibly indicating that the adverse constraints were caused by two strong interactions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For Ss APN, additional extended phosphinic analogs, which were at least tripeptides, reportedly exhibited similar levels of inhibition. 55 , 56 Doubled modifications were less favorable for Nm APN than for Ss APN, possibly indicating that the adverse constraints were caused by two strong interactions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The following substrates were used for the determination of enzymatic activity: H-Ala-pNA-HCl for APN; H-Glu-pNA-2HCl (both from Bachem, Weil am Rhein, Germany) for APA; H-Leu-pNA-HCl (Sigma, Taufkirchen, Germany) plus RB3014 [specific inhibitor of APN, kindly provided by B.P. Roques (Département de Pharmacochimie Moléculaire et Structurale INSERM U266 - CNRS UMR 8600 UFR des Sciences Pharmaceutiques et Biologiques, Paris, France) ( 42 ) ] for IRAP; Mca-APK (Dnp; Enzo/Biomol, Hamburg, Germany) for ACE2. All the assays were carried out in 50 mM HEPES buffer containing 200 mM NaCl, 10 μM ZnCl 2 and 1% DMSO pH 6.8.…”
Section: Methodsmentioning
confidence: 99%
“…Incorporating (R)- β 2 hVal 1 and Aia 4 -Gly 5 gave a compound that is highly selective and stable and has a high inhibitory effect (AL-40, Figure 9) [168, 170]. Ang IV itself is only a weak inhibitor of the catalytic activity of IRAP, as has been shown by experiments with the metabolically stable tritiated Ang IV analogue [ 3 H]AL-11, in combination with the selective AP-N inhibitor 7B which is a phosphinic transition-state analogue [171] and in the absence of metal chelators. Adding metal chelators creates the apoform of IRAP [167, 172], and it is important to note that the active form and apoforms of IRAP react differently [173].…”
Section: Inhibitors Of Insulin-regulated Aminopeptidasementioning
confidence: 99%
“…Previous conformational analyses of Ang II suggested that such a macrocyclic system would tend to adopt an inverse γ -turn [181, 182], and the replacement of His-Pro-Phe by a 2-(aminomethyl)phenylacetic acid moiety designed to mimic an inverse γ -turn resulted in compound 9 (Figure 10). This compound has a K i value of 44 nM and a much simpler structure than previous candidates [171]. …”
Section: Inhibitors Of Insulin-regulated Aminopeptidasementioning
confidence: 99%